2008
DOI: 10.1175/2007jas2394.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Cloud Systems over ARM SGP

Abstract: Increased observational analyses provide a unique opportunity to perform years-long cloud-resolving model (CRM) simulations and generate long-term cloud properties that are very much in demand for improving the representation of clouds in general circulation models (GCMs). A year 2000 CRM simulation is presented here using the variationally constrained mesoscale analysis and surface measurements. The year-long (3 January–31 December 2000) CRM surface precipitation is highly correlated with the Atmospheric Radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Previous studies on the differences between the 2‐D and the three dimensional (3‐D) CRM simulations showed that the 3‐D simulations had superior performances over the 2‐D simulations in various aspects [e.g., Donner et al ., ; Petch and Gray , ; Phillips and Donner , ; Petch et al ., ]. However, the cost‐effectiveness of the 2‐D CRM simulation is still a major advantage and the 2‐D approach is still adopted in some recent studies for year‐long or multiyear simulations [e.g., Wu and Park , ; Henderson and Pincus , ; Blossey et al ., ]. In addition, the 2‐D CRMs are still used in most MMF configurations so the 2‐D CRM simulations are appropriate and relevant in this context.…”
Section: Case Studies and Experiments Designmentioning
confidence: 99%
“…Previous studies on the differences between the 2‐D and the three dimensional (3‐D) CRM simulations showed that the 3‐D simulations had superior performances over the 2‐D simulations in various aspects [e.g., Donner et al ., ; Petch and Gray , ; Phillips and Donner , ; Petch et al ., ]. However, the cost‐effectiveness of the 2‐D CRM simulation is still a major advantage and the 2‐D approach is still adopted in some recent studies for year‐long or multiyear simulations [e.g., Wu and Park , ; Henderson and Pincus , ; Blossey et al ., ]. In addition, the 2‐D CRMs are still used in most MMF configurations so the 2‐D CRM simulations are appropriate and relevant in this context.…”
Section: Case Studies and Experiments Designmentioning
confidence: 99%
“…Ferrier et al, 1995;Tao et al, 2003;Hong et al, 2004;Leung et al, 2006;Wu et al, 2008). However, even in highly sophisticated models, the representation of clouds remains a challenge (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The horizontal grid size is 3 km and the vertical grid of 52 levels is 100 m at the surface, 550-850 m between 5 and 12 km, and 1500 m at the model top. The simulation time step is 15 s. The model setting of the year-long (i.e., January 3-December 31, 2000) CRM simulation is basically the same as the CRM simulation by Wu et al (2008). The year-long CRM simulation is forced by the evolving temperature and moisture forcing which is kept constant for an hour around the observed time.…”
Section: Isu Cloud-resolving Modelmentioning
confidence: 99%
“…The CRM simulations have been assessed with various observations in terms of atmospheric thermodynamic properties, atmospheric radiation, precipitation, and surface fluxes in the tropics during the Global Atmospheric Research Program Atlantic Tropical Experiment (GATE) (e.g., Xu and Randall 1996;Grabowski et al 1996), Tropical Ocean Global Atmosphere Coupled Ocean Atmosphere Response Experiment (TOGA COARE) (e.g., Wu et al 1998;Li et al 1999;Wu and Moncrieff 2001), and ARM (e.g., Xu et al 2002;Wu et al 2007Wu et al , 2008. Grabowski et al (1996Grabowski et al ( , 1998Grabowski et al ( , 1999 conducted 2-dimensional (2D) and 3-dimensional (3D)…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation